Effect of lead on root growth - FAHR, Mouna; Laplaze, Laurent; BENDAOU, Najib; HOCHER, Valerie; EL MZIBRI, Mohamed; BOGUSZ, DIDIER; SMOUNI, Abdelaziz (Frontiers in Plant Science, 2013)
Lead (Pb) is one of the most widespread heavy metal contaminants in soils. It is highly toxic to living organism. Pb has no biological function but can cause morphological, physiological and biochemical dysfunctions in plants. Plants have developed a wide range of tolerance mechanisms that are activated in response to lead exposure. Pb affects plants primarily through their root systems. Plant roots rapidly respond either (i) by the synthesis and deposition of callose, creating a barrier that stops lead entering (ii) through the uptake of large amounts of Pb and its sequestration in the vacuole accompanied by changes in root growth and branching pattern or (iii) by its translocation to the aboveground parts of plant in the case of hyperaccumulators plants. Here we review the interactions of roots with the presence of Pb in the rhizosphere and the effect of Pb on the physiological and biochemical mechanisms of root development.